The role of sociological research in the planning of advertising campaigns - A. A. Komarova; V. G. Novikov; M. Yu. Zakharov (Вестник университета)
The role of sociological research in the strategy of planning advertising campaigns has been has been considered. Sociological research is the main supplier of data on the behavior of the target audience, its quantity, and the structure of its media consumption. On the basis of sociological data, a decision-making process is taking place on the choice of the required type of media, or media mix, the start time of the campaign and the frequency of advertising. With the assistence of sociological measurements delivered on an ongoing basis, calculate the efficiency of media indicators of advertising goods and services. One of the research areas is the evaluation of the content of advertising communication by consumers, the quality of creativity and the way of presenting information, the recognition of the key idea of advertising communication. For the needs of the advertising market, both qualitative and quantitative sociological studies are used.